A Rapid Antimicrobial Susceptibility Test for Determining Yersinia pestis Susceptibility to Doxycycline by RT-PCR Quantification of RNA Markers - Shifman, Ohad; Steinberger-Levy, Ida; Aloni-Grinstein, Ronit; Gur, David; Aftalion, Moshe; Ron, Izhar; Mamroud, Emanuelle; Ber, Raphael; Rotem, Shahar (Frontiers in Microbiology, 2019)
Great efforts are being made to develop new rapid antibiotic susceptibility tests to meet the demand for clinical relevance versus disease progression. This is important especially in diseases caused by bacteria, such as Yersinia pestis, the causative agent of plague, which grows rapidly in vivo but relatively slow in vitro. This compromises the ability to use standard growth-based susceptibility tests to obtain rapid and proper antibiotic treatment guidance. Using our previously described platform of quantifying antibiotic-specific transcriptional changes, we developed a molecular test based on changes in expression levels of doxycycline response-dependent marker genes that we identified by transcriptomic analysis. This enabled us to determine the minimal inhibitory concentration of doxycycline within 7 h compared to the 24 h required by the standard CLSI test. This assay was validated with various Y. pestis strains. Moreover, we demonstrated the applicability of the molecular test, combined with a new rapid bacterial isolation step from blood cultures, and show its relevance as a rapid test in clinical settings.